ARTIFICIAL INTELLECTUAL (AI) DEVELOPMENT POLICY OF SOME COUNTRIES AND EXPERIMENTAL LESSONS IN BUILDING AI POLICY FOR VIETNAM - PhD. Nguyen Xuan Thuy, PhD. Bui Nguyen Khanh, PhD. Nguyen Quoc SPhD. Dao Ha Vinhuu (International Journal of Advanced Science and Technology, 2020)
It may not be possible to imagine exactly how Artificial Intelligence will affect the future but it will certainly change the world. Now researchers are building the ability to "enhance learning" for AI. This is a training method that allows AI models to learn lessons from its own past experience. This means that the above models are able to think of different methods to achieve the best results. In the coming years, they will be integrated with more hardware and software solutions, from the ability of AI to adjust the time to turn on traffic lights to optimize traffic flow to unmanned aircraft driven by AI, even some countries are studying law and ethical issues in developing AI in many areas. Above, the author provides some AI development policies of some countries in the world. Thereby, Vietnam may learn from experience for developing AI in Vietnam in the next time.